Particle Size-Specific Distributions and Preliminary Exposure Assessments of Organophosphate Flame Retardants in Office Air Particulate Matter - Yang, Fangxing; Ding, Jinjian; Huang, Wei; Xie, Wei; Liu, Weiping (Environmental science & technology, 2014)
In this study, the concentrations, size-specific distributions, and preliminary exposure assessments of 10 organophosphate flame retardants (OPFRs) were investigated in suspended particulate matter collected from offices. OPFRs were detected in a range of 5.00–147.77 ng/m3. Tri(chloropropyl) phosphate (TCPP) was the most abundant analog followed by tri(2-chloroethyl) phosphate (TCEP) and triphenyl phosphate (TPhP). Chlorinated OPFRs (TCPP, TCEP, and tris(1,3-dichloroisopropyl) phosphate (TDCPP)) contributed to about 77% of the total OPFRs. Size-specific distributions revealed that TCEP, tri-n-propyl phosphate (TnPP), TCPP, and tri-n-butyl phosphate (TnBP) shared a similar distribution pattern with a peak in the fraction 4.7–5.8 μm. A peak was also found in the distributions of tricresyl phosphate (TCrP), 2-ethylhexyl diphenyl phosphate (EHDPP), and tri(2-ethylhexyl) phosphate (TEHP) but in different fractions. A bimodal distribution was observed for TDCPP, TPhP, and tributoxyethyl phosphate (TBEP). The results of mass median aerodynamic diameter (MMAD) indicated that TDCPP, TCrP, and TEHP were mainly located on ultrafine particles (≤1 μm), while TnPP, TBEP, and EHDPP mainly on fine particles (≤2.5 μm). Furthermore, MMADs of OPFRs were found to be positively correlated with their vapor pressures (Vp) (p < 0.01), indicating that OPFR analogs with low Vp were inclined to adsorb on small size particles. Preliminary exposure assessments suggested a low risk of exposure to OPFRs for people working in such offices, and inhaled OPFRs would mainly deposit in the head region of the respiratory tract.